(untitled) (International Journal of Engineering Sciences & Management Research, 2017)
This article addresses some of cinema’s anthropological and historical backgrounds. Etymology is also taken into account. Cinema is a hybrid kind of art which deals directly with movement. Having its roots in Ancient times, maybe in pre-history, cinema stems directly from photography. Its hybridism is due to the fact that it combines features of architecture, painting, sculpture, music, poetry and dance (the six classical arts that are historically precedent in relation to cinema) into a single work of art – hence the title “seventh art”. The article also stresses the fact that technological progress and innovation in general (e.g., 3D film) do not necessarily mean quality improvement; paradoxically as it may seem, the opposite is closer to the truth, since the excess of facilities becomes a difficulty in itself – a rule valid for cinema, the other arts and each and every human activity in general.